Radio Fatwa: Islamic Tanya-Jawab Programmes on Radio Dakwah - S. Sunarwoto (Al-Jami'ah Research Centre, 2012)
The present article is a study of radio fatwa in Indonesia with special reference to the Tanya-Jawab genres in radio dakwah. The concept of fatwa has changed over time. Such Islamic Tanya-Jawab programmes broadcast on radio dakwah are important to understand how fatwa is disseminated by means of media, since Islamic Tanya-Jawab programmes can be considered as part of fatwa. These programmes give not only information about Islam, but also become a forum in which interpretation of Islam takes place. This can be seen in the discussion on the Islamic ruling on eating “dog meat”, in which interpretation of Islamic law is highly contested.[Artikel ini mendiskusikan radio fatwa di Indonesia, utamanya tentang program tanya-jawab yang disiarkan radio dakwah. Konsep fatwa terus berubah dan program tanya-jawab merupakan salah satu cara bagaimana fatwa disebarluaskan melalui berbagai media. Penulis berpendapat bahwa program Tanya-Jawab dapat disebut sebagai salah satu bentuk fatwa. Ini karena program tersebut tidak saja mengetengahkan informasi mengenai Islam, namun juga interpretasi mengenai Islam. Perdebatan mengenai hukum memakan daging anjing merupakan salah satu contoh isu kontroversial yang akan dijelaskan melalui artikel ini.]